Pt thin-film resistance temperature detector on flexible Hastelloy tapes. (February 2021) - Shao, Lei; Zhao, Xiaohui; Gu, Shipeng; Ma, Yaping; Liu, Yang; Deng, Xinwu; Jiang, Hongchuan; Zhang, Wanli
Abstract: Platinum (Pt) thin-film resistance temperature detector was fabricated on the flexible Hastelloy tapes using magnetron sputtering and MEMS processes. NiCrAlY buffer layer and AlON/Al2 O3 insulating layer were deposited on the tapes for stress release and electrical insulation. Post annealing was applied to improve the stability of the sensors. The performance of the sensor was calibrated with temperature up to 550 °C. Compared with the sensor on the alumina ceramic substrate, the sensor on Hastelloy tapes have much smaller thermal hysteresis, higher linearity and excellent stability. Moreover, this flexible sensor can be easily integrated with the metallic components by the welding and the maximum curvature of the sensor is 2 cm −1 . This Pt thin-film temperature sensor has great potential in the surface temperature measurement of hot components in harsh environment. Highlights: This Hastelloy tape based RTD has small thermal hysteresis, higher linearity and excellent stability. AlON/Al2 O3 structure ensures the electrical insulation between the Pt film and the metallic substrate. This flexible sensor can be easily integrated with metallic components for surface temperature measurement.